2017
DOI: 10.1111/dom.13053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of liraglutide on ectopic fat in polycystic ovary syndrome: A randomized clinical trial

Abstract: Women with polycystic ovary syndrome (PCOS) were treated with the GLP-1 receptor agonist liraglutide to investigate the effect on liver fat content, visceral adipose tissue (VAT) and the prevalence of nonalcoholic fatty liver disease (NAFLD). In a double-blind, placebo-controlled, randomized clinical trial 72 women with PCOS, with a BMI > 25 kg/m and/or insulin resistance, were treated with liraglutide or received placebo 1.8 mg/d (2:1) for 26 weeks. Liver fat content was assessed by HMR spectroscopy, VAT by M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 15 publications
4
98
0
4
Order By: Relevance
“…The study achieved the primary endpoint, demonstrating that 39% of patients in the liraglutide group compared to 9% in the placebo group met the primary endpoint of histological resolution of NASH without worsening of fibrosis (relative risk of The majority of studies that investigated changes in hepatic fat content with liraglutide or exenatide demonstrated benefit, and all studies of 16 weeks duration or longer with steatosis measured via imaging as an endpoint demonstrated benefit. Magnitude of benefit was approximately 30-45% relative reduction in fat content in most studies (19,22,34,44). Similarly, the majority of studies investigating serum markers of liver injury (ALT, AST, or GGT) demonstrated a benefit of liraglutide, with effect sizes ranging from quite modest (e.g., 5 U/L or less reduction in ALT) to ≥20 U/L and thus likely to be clinically meaningful.…”
Section: No Data No Datamentioning
confidence: 95%
See 1 more Smart Citation
“…The study achieved the primary endpoint, demonstrating that 39% of patients in the liraglutide group compared to 9% in the placebo group met the primary endpoint of histological resolution of NASH without worsening of fibrosis (relative risk of The majority of studies that investigated changes in hepatic fat content with liraglutide or exenatide demonstrated benefit, and all studies of 16 weeks duration or longer with steatosis measured via imaging as an endpoint demonstrated benefit. Magnitude of benefit was approximately 30-45% relative reduction in fat content in most studies (19,22,34,44). Similarly, the majority of studies investigating serum markers of liver injury (ALT, AST, or GGT) demonstrated a benefit of liraglutide, with effect sizes ranging from quite modest (e.g., 5 U/L or less reduction in ALT) to ≥20 U/L and thus likely to be clinically meaningful.…”
Section: No Data No Datamentioning
confidence: 95%
“…Multiple publications have reported beneficial effects to reduce liver fat content and improve ALT, and one study has suggested a benefit in reducing progression of fibrosis (5,10,34,50). Twenty publications reported the effects of a GLP-1 analog on liverrelated endpoints; 12 of these investigated liraglutide (5,6,11,19,20,22,34,44,50,60,65,66), and 8 investigated exenatide (10,13,14,17,18,55,56,58). Four of these reported randomized, controlled, double-blind studies of liraglutide with a placebo (n = 3) or active (n = 1) comparator, and only one of these, the "Liraglutide Safety and Efficacy in Patients with Non-alcoholic Steatohepatitis (LEAN)" study, assessed histological endpoints using biopsy.…”
Section: Glp-1 Agonistsmentioning
confidence: 99%
“…Der Effekt von Antidiabetika wie Liraglutid und Empagliflozin ist Gegenstand von Studien. Diese weisen vereinzelt positive Daten zur Reduktion von Gewicht, Hyperandrogenämie, Anovulation und zur Schwangerschaftsrate unter IVF auf [16][17][18][19][20]. Der Einsatz ist derzeit als experimentell zu betrachten und für die Patientinnen auch im Rahmen der Indikation der Lifestyle-Medikation oder eines Off-Label-Use kostenintensiv.…”
Section: Ausblickunclassified
“…(15) But negative results have also been reported with sitagliptin in open-label studies (16,17) and in all three placebo-controlled trials. (18)(19)(20) Negative studies have been also reported with liraglutide, (20,21) but most have been positive with an improvement in hepatic steatosis (HS) (22)(23)(24)(25)(26)(27)(28) or liver histology. (29,30) This is usually proportional to the magnitude of weight loss, as reported for other short- (31) and long-acting (32) GLP-1RAs.…”
Section: See Article On Page 2414mentioning
confidence: 99%